Estimated annual and lifetime labor productivity in the United States, 2016: implications for economic evaluations. (3rd June 2019) - Grosse, Scott D.; Krueger, Kurt V.; Pike, Jamison
Abstract: Background: Human-capital based lifetime productivity estimates are frequently used in cost-of-illness (COI) analyses and, less commonly, in cost-effectiveness analyses (CEAs). Previous US estimates assumed that labor productivity and real earnings both grow by 1% per year. Objectives: This study presents estimates of annual and lifetime productivity for 2016 using data from the American Community Survey, the American Time Use Survey, and the Current Population Survey, and with varying assumptions about real earnings growth. Methods: The sum of market productivity (gross annual personal labor earnings adjusted for employer-paid benefits) and the imputed value of non-market time spent in household, caring, and volunteer services was estimated. The present value of lifetime productivity at various ages was calculated for synthetic cohorts using annual productivity estimates, life tables, discount rates, and assumptions about future earnings growth rates. Results: Mean annual productivity was $57, 324 for US adults in 2016, including $36, 935 in market and $20, 389 in non-market productivity. Lifetime productivity at birth, using a 3% discount rate, is roughly $1.5 million if earnings grow by 1% per year and $1.2 million if future earnings growth averages 0.5% per year. Conclusions: Inclusion of avoidable productivity losses in societal-perspective CEAs of health interventions is recommended in new US cost-effectiveness guidelines. However, estimates vary depending on whether analysts choose to estimate total productivity or just market productivity, and on assumptions made about growth in future productivity and earnings.